Genetic distance between broodstocks of the marine shrimp Litopenaeus vannamei (Decapoda, Penaeidae) by mtDNA analyses - Francisco,Ana Karina de (2005)
In the constantly growing Brazilian shrimp industry the evaluation of genetic relationships between broodstocks is an useful tool for shrimp culture management programs. We established the genetic relationships between five broodstocks of the white marine shrimp Litopenaeus vannamei (Penaeidae) based on the sequencing of the mtDNA 16S rRNA and cytochrome oxidase I (COI) regions. Although no divergence was found between the broodstocks for the highly conservative 16S rRNA gene, we did find an 8.2% distance between L. vannamei and the Farfantepenaeus subtilis. Analyses of the COI region showed genetic distances of only 0.2 to 1% between the broodstocks, which contrasted with the 10.9% mean distance found between L. vannamei and F. subtilis. The small genetic distance values obtained may be related to genetic drift or a founder effect that occurred during broodstocks establishment. The mtDNA analysis was able to characterize the genetic divergence between the broodstocks studied and could be helpful for defining better management strategies of these crustacea.